Paul Ricoeur's idea of reference : the truth as non-reference - Ivić, Sanja, (Value Inquiry Book Series, 2019)
This book investigates the importance of Ricoeur's hermeneutics and poetics in rethinking humanities. In particular, Ricoeur's insights on reference as refiguration and his idea of interpretation as a triadic process (which consists of mimesis 1 - prefiguration, mimesis 2 - configuration, and mimesis 3 - refiguration) will be applied to philosophy of science and to literary and historical texts. It will be shown that Ricoeur's idea of emplotment can be extended and applied to scientific, literary and historical texts. This multidisciplinary research will include philosophy of science, metaphysics, hermeneutics, and literary theory.